MicroRNA 299-3p modulates replicative senescence in endothelial cells - Jong, Hui-Lan; Mustafa, Mohd Rais; Vanhoutte, P.M.; AbuBakar, Sazaly; Wong, P.F. (2013)
MicroRNAs (miRNAs) regulate various cellular processes. While several genes associated with replicative senescence have been described in endothelial cells, miRNAs that regulate these genes remain largely unknown. The present study was designed to identify miRNAs associated with replicative senescence and their target genes in human umbilical vein endothelial cells (HUVECs). An integrated miRNA and gene profiling approach revealed that hsa-miR-299-3p is upregulated in senescent HUVECs compared with the young cells, and one of its target genes could be IGF1. IGF1 was upregulated in senescent compared with young HUVECs, and knockdown of hsa-miR-299-3p dose-dependently increased the mRNA expression of IGF1, more significantly observed in the presenescent cells (passage 19) compared with the senescent cells (passage 25). Knockdown of hsa-miR-299-3p also resulted in significant reduction in the percentage of cells positively stained for senescence-associated Î²-galactosidase and increases in cell viability measured by MTT assay but marginal increases in cell proliferation and cell migration capacity measured by real-time growth kinetics analysis. Moreover, knockdown of hsa-miR-299-3p also increased proliferation of cells treated with H2O2 to induce senescence. These findings suggest that hsa-miR-299-3p may delay or protect against replicative senescence by improving the metabolic activity of the senesced cells but does not stimulate growth of the remaining cells in senescent cultures. Hence, these findings provide an early insight into the role of hsa-miR-299-3p in the modulation of replicative senescence in HUVECs.